Diel variation in movement patterns and habitat use by the Iberian endemic Cabrera vole: Implications for conservation and monitoring - Grácio, Ana Rita (2018)
Understanding variations in animal movement and habitat selection behaviour over fine spatial and temporal scales remains a particularly challenging goal in ecology and conservation. Here we document for the first time the diel variations in movement patterns and habitat use by wild-ranging Cabrera voles in fragmented Mediterranean farmland, based on radiotracking data (2006–2008) of 25 adult individuals occupying stable home-ranges in vegetation mosaics dominated by wet grasses and shrubs. Results indicated that the proportion of time animals spent moving, the distance moved, and the selection strength of main vegetation types were closely linked behavioural traits, which varied considerably across different periods of the 24-h cycle. In general, voles moved more frequently and over larger distances during daytime (between 06 h15–22 h00), which was when wet grasses were also used more intensively. These patterns were generally consistent across seasons, though during the dry season there was some tendency for a decrease in movement activity during the hottest hours of the day (between 10h15–14h00), with peaks around crepuscular hours (06h15–10 h00 and 18h15–22h00). Overall, our study provides evidence that Cabrera voles may show notable shifts in habitat use and movement patterns on a finer scale than previously considered. This supports the idea that knowledge of the diel variations in species movement-habitat relationships should strongly contribute to improving local habitat management, as well as effective sampling and monitoring programs targeting the species.